A hard wear-resistant non-PVC environmentally friendly stone plastic floor and preparation method thereof

By using materials such as degradable PBAT resin and functionalized polyurethane elastomers in stone plastic floors, the potential risks of PVC stone plastic flooring to the environment and human health are solved, and a more environmentally friendly and durable stone plastic flooring is achieved.

CN119777555APending Publication Date: 2025-04-08ZHEJIANG LEYI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411979094.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing PVC stone plastic flooring is non-degradable and contains harmful chemicals, which leads to environmental pollution and human health risks, and is difficult to recycle and deal with.

Method used

Degradable PBAT resin is used to replace PVC, and a specific enhancement additive is added to the substrate layer, and a wear-resistant layer is made with functionalized polyurethane elastomer and modified filler to improve the wear resistance and mechanical properties of stone plastic floors.

Benefits of technology

It realizes the environmental protection and durability of stone plastic flooring, reduces the risk of environmental pollution, improves the hardness and scratch resistance of the material, and extends the service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a hard wear-resistant non-PVC environmentally friendly stone plastic floor and a preparation method thereof, and belongs to the technical field of building materials. The hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises a wear-resistant layer, a color film layer and a substrate layer from top to bottom, and is prepared by hot pressing and compounding; wherein the wear-resistant layer comprises the following raw materials: functionalized polyurethane elastomer, modified filler, antioxidant; the substrate layer comprises the following raw materials: PBAT resin, heavy calcium carbonate, mica powder, reinforcing additive, stabilizer, plasticizer. Compared with the existing PVC stone plastic floor, the stone plastic floor prepared by the present invention is not only green and environmentally friendly, but also has excellent mechanical properties and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a hard wear-resistant non-PVC environmentally friendly stone plastic floor and a preparation method thereof. Background Art

[0002] Stone plastic floor is a modern building decoration material, which combines the characteristics of natural stone and plastic materials, has good waterproof and moisture-proof performance, compression resistance, anti-slip performance, wear resistance and corrosion resistance, etc., and is easy to clean daily, and is widely used in residential, shopping malls and other public places. In addition, stone plastic floor is easy to cut and splice, simple to install and construct, with low maintenance cost and long service life. It can also imitate the appearance of various materials, such as marble texture, wood texture, carpet texture, etc., with a wide variety of colors and patterns, and can even be customized to meet the needs of different consumers.

[0003] At present, the main stone plastic floor is PVC stone plastic floor, which uses PVC resin and stone powder such as calcium carbonate as raw materials, and can also add additives such as stabilizers, lubricants, plasticizers, etc., and is made through calendering, extrusion, hot pressing and other processes. For example, Chinese patent CN107627687A discloses a PVC stone plastic floor and a manufacturing method thereof, wherein the PVC stone plastic floor is hot-pressed and composited by a wear-resistant layer, a decorative layer and a base layer; wherein the base layer includes raw materials such as PVC resin, calcium carbonate, stabilizers, lubricants, carbon black, dioctyl terephthalate, etc., and the wear-resistant layer is a coating layer containing inorganic filler particles; the stone plastic floor has good mildew resistance, stain resistance, wear resistance, and scratch resistance. Chinese patent CN109057241A discloses a stone plastic floor and a preparation method thereof, comprising the following steps: adding PVC resin and heavy calcium carbonate into a mixer and heating and mixing them, adding calcium zinc stabilizer, auxiliary polyacrylate / elastic chlorinated polyethylene, PVC lubricant, camphor wood fiber and other raw materials into the mixer and continuing to heat and mix them, cooling them, adding the mixed materials into an extruder for extrusion molding to obtain a substrate layer; hot pressing the substrate layer and the decorative surface layer, and then performing board separation, health care, and slotting treatment to obtain the stone plastic floor; the stone plastic floor has good mechanical strength, bending elastic modulus, dimensional stability, etc., and also has good health functions such as insect repellent, antibacterial, and sleep-aiding.

[0004] Although PVC stone plastic floor has many advantages mentioned above, it is difficult to recycle because PVC is a non-degradable plastic and contains a large amount of chlorine. It will release toxic and harmful gases when it is burned at high temperature. Improper treatment can easily cause environmental pollution and harm human health. In addition, phthalic acid plasticizers are commonly used in PVC stone plastic floor, which may precipitate from the floor over time, affecting indoor air quality and having adverse effects on human health. Therefore, it is urgent to provide an environmentally friendly stone plastic floor made of non-PVC material, which has good wear resistance and scratch resistance. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a hard wear-resistant non-PVC environmentally friendly stone plastic floor, which comprises a wear-resistant layer, a color film layer and a substrate layer from top to bottom, wherein the substrate layer adopts a degradable PBAT resin to replace PVC, and is further made by adding specific reinforcing additives, stabilizers, plasticizers, etc., which is more green and environmentally friendly and has excellent mechanical properties; the wear-resistant layer is made of a specific functionalized polyurethane elastomer and a modified filler, which significantly improves the wear resistance of the stone plastic floor.

[0006] A hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises, from top to bottom, a wear-resistant layer, a color film layer and a substrate layer; the wear-resistant layer comprises the following raw materials: functionalized polyurethane elastomer, modified filler, antioxidant; the substrate layer comprises the following raw materials: PBAT resin, heavy calcium carbonate, mica powder, reinforcing additive, stabilizer, plasticizer.

[0007] Preferably, the wear-resistant layer is made of the following raw materials in parts by weight:

[0008] 90-100 parts by weight of functionalized polyurethane elastomer, 3-7 parts by weight of modified filler, and 0.3-0.6 parts by weight of antioxidant.

[0009] Preferably, the functionalized polyurethane elastomer is prepared by the following method:

[0010] 25-35 parts by weight of 1,3,5,7,9-pentamethylcyclopentasiloxane and 10-20 parts by weight of allyl succinic anhydride are added to 100-150 parts by weight of N,N-dimethylformamide, heated under nitrogen protection, then 0.1-0.3 parts by weight of Custer catalyst are added for reaction, and N,N-dimethylformamide is recovered by vacuum distillation to obtain succinic anhydride grafted cyclopentasiloxane; 10-15 parts by weight of succinic anhydride grafted cyclopentasiloxane, 6-10 parts by weight of heptamethylphenyl cyclotetrasiloxane, and 0.1-0.2 parts by weight of tetramethylammonium hydroxide are added to 70-100 parts by weight of N,N -dimethylformamide, heating for reaction, then adding 0.1-0.3 parts by weight of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to continue the reaction, recovering N,N-dimethylformamide by reduced pressure distillation to obtain modified polysiloxane; 10-15 parts by weight of polytetrahydrofuran ether diol, 20-30 parts by weight of diphenylmethane-4,4'-diisocyanate, 4-6 parts by weight of modified polysiloxane, 2-4 parts by weight of 1,4-butanediol and 0.1-0.2 parts by weight of dibutyltin dilaurate are mixed, heating for reaction, and drying after completion to obtain a functionalized polyurethane elastomer.

[0011] Preferably, the modified filler is prepared by the following method:

[0012] 1-2 parts by weight of N-aminoethyl-3-aminopropylmethyldimethoxysilane is added to 20-30 parts by weight of 50-70wt% ethanol aqueous solution, heated and stirred, then 2-4 parts by weight of nano-alumina and 70-80 parts by weight of anhydrous ethanol are added and stirred continuously, filtered and dried to obtain surface-treated nano-alumina; 0.5-0.8 parts by weight of 2-furanacetic acid, 2-3 parts by weight of surface-treated nano-alumina and 0.03-0.06 parts by weight of 4-dimethylaminopyridine are added to 15-30 parts by weight of tetrahydrofuran, heated for reaction under nitrogen protection, filtered and dried to obtain a modified filler.

[0013] The present invention adopts functionalized polyurethane elastomer and modified filler as main raw materials to prepare wear-resistant layer, which effectively improves the wear resistance of stone plastic floor. Firstly, in the preparation process of functionalized polyurethane elastomer, modified polysiloxane adopts succinic anhydride grafted cyclopentasiloxane and heptamethylphenyl cyclotetrasiloxane as monomers, and the phenyl structure in modified polysiloxane gives polyurethane elastomer higher rigidity and modulus, which helps to enhance the hardness and compressive strength of the material, thereby improving the wear resistance; succinic anhydride group increases the cross-linking point of polyurethane elastomer, which helps to undergo cross-linking reaction with modified filler later, and enhances its interface bonding force. Secondly, in the preparation process of modified fillers, amino functional groups are introduced into nano-alumina after surface treatment with N-aminoethyl-3-aminopropylmethyldimethoxysilane. These amino groups can react with the carboxyl groups in 2-furanacetic acid under the catalysis of 4-dimethylaminopyridine to form stable chemical bonds. The modified filler not only has high hardness and wear resistance, but also can cross-link with the succinic anhydride groups in the functionalized polyurethane elastomer through the furan groups it contains, thereby enhancing the interface bonding force. Moreover, the formation of a cross-linked network can inhibit the relative slip between molecular chains, thereby further improving the wear resistance of the stone plastic floor.

[0014] In summary, the synergistic effect between functionalized polyurethane elastomer and modified filler is the key to improving the wear resistance of SPC flooring. The introduction of modified filler increases the hardness and scratch resistance of the material, thereby improving the wear resistance. The succinic anhydride group in the functionalized polyurethane elastomer reacts with the furan group in the modified filler to form a cross-linked network structure, which helps to improve the comprehensive performance of the wear-resistant layer, thereby reducing wear. The flexibility and resilience of the polyurethane elastomer itself also make the material less likely to crack during long-term use, ensuring the durability of the SPC flooring.

[0015] Preferably, the functionalized polyurethane elastomer is prepared by the following method:

[0016] 25-35 parts by weight of 1,3,5,7,9-pentamethylcyclopentasiloxane and 10-20 parts by weight of allyl succinic anhydride are added to 100-150 parts by weight of N,N-dimethylformamide, and heated to 70-80°C at 200-300rpm under nitrogen protection, and then 0.1-0.3 parts by weight of Custer catalyst are added to keep the temperature for reaction for 2-4h, and N,N-dimethylformamide is recovered by vacuum distillation to obtain succinic anhydride grafted cyclopentasiloxane; 10-15 parts by weight of succinic anhydride grafted cyclopentasiloxane, 6-10 parts by weight of heptamethylphenyl cyclotetrasiloxane, and 0.1-0.2 parts by weight of tetramethylammonium hydroxide are added to 70-100 parts by weight of N,N-dimethylformamide, and heated to 65-7 5°C, 200-300rpm, react for 0.5-1.5h, then add 0.1-0.3 parts by weight of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and continue to react for 0.4-0.6h, and recover N,N-dimethylformamide by reduced pressure distillation to obtain modified polysiloxane; 10-15 parts by weight of polytetrahydrofuran ether diol, 20-30 parts by weight of diphenylmethane-4,4'-diisocyanate, 4-6 parts by weight of modified polysiloxane, 2-4 parts by weight of 1,4-butanediol and 0.1-0.2 parts by weight of dibutyltin dilaurate are mixed, reacted at 70-80°C, 100-200rpm for 2-4h, and dried after completion to obtain a functionalized polyurethane elastomer.

[0017] Preferably, the modified filler is prepared by the following method:

[0018] 1-2 parts by weight of N-aminoethyl-3-aminopropylmethyldimethoxysilane is added to 20-30 parts by weight of 50-70wt% ethanol aqueous solution, stirred at 45-55°C and 100-300rpm for 10-30min, then 2-4 parts by weight of nano-alumina and 70-80 parts by weight of anhydrous ethanol are added and stirred for 1-2h, filtered and dried to obtain surface-treated nano-alumina; 0.5-0.8 parts by weight of 2-furanacetic acid, 2-3 parts by weight of surface-treated nano-alumina and 0.03-0.06 parts by weight of 4-dimethylaminopyridine are added to 15-30 parts by weight of tetrahydrofuran, reacted at 50-60°C under nitrogen protection for 10-15h, filtered and dried to obtain a modified filler.

[0019] Preferably, the antioxidant is at least one of antioxidant 1076, antioxidant 1010, and antioxidant DSTDP.

[0020] Preferably, the substrate layer is made of the following raw materials in parts by weight:

[0021] 30-50 parts by weight of PBAT resin, 50-70 parts by weight of heavy calcium carbonate, 10-20 parts by weight of mica powder, 3-5 parts by weight of reinforcing agent, 0.1-0.3 parts by weight of stabilizer, and 0.2-0.4 parts by weight of plasticizer.

[0022] Preferably, the reinforcing aid is EMA-g-GMA and / or EVA-g-MAH.

[0023] Preferably, the reinforcing aid is a mixture of EMA-g-GMA and EVA-g-MAH in a weight ratio of 3:1-3.

[0024] The invention further improves the tensile strength and impact strength of the stone plastic floor by adding reinforcing additives (EMA-g-GMA and EVA-g-MAH) into the raw material formula of the substrate layer.

[0025] On the one hand, the epoxy groups in EMA-g-GMA and the maleic anhydride groups in EVA-g-MAH are highly chemically reactive and can form covalent bonds between the active groups on the surface of heavy calcium carbonate / mica powder, such as hydroxyl groups, and the polar groups in the PBAT matrix, thereby effectively improving the interfacial bonding between heavy calcium carbonate / mica powder and the PBAT matrix. This enhanced interfacial bonding can effectively transfer stress, prevent stress concentration around inorganic particles, reduce the possibility of crack propagation, and thereby improve the tensile properties and impact resistance of the material. On the other hand, the polyolefin backbone of EMA-g-GMA and EVA-g-MAH has good compatibility with the PBAT matrix, which can promote the uniform dispersion of inorganic particles in the matrix, avoid particle agglomeration, and further improve the overall mechanical properties of the material. At the same time, the two graft copolymers can also form a three-dimensional network structure through cross-linking reactions, thereby increasing the energy absorption capacity and toughness of the material and delaying crack propagation. The synergistic effect of EMA-g-GMA and EVA-g-MAH not only enhances the interfacial bonding / compatibility and chemical reactivity between the inorganic particles and the PBAT matrix, but also improves the rigidity and modulus of the material, making the SPC floor exhibit better tensile strength and impact resistance when subjected to external forces, giving it excellent mechanical properties and durability in practical applications.

[0026] Preferably, the stabilizer is any one of N,N'-di(2,6-diisopropylphenyl)carbodiimide, polycarbodiimide, and N,N'-diisopropylcarbodiimide.

[0027] Preferably, the plasticizer is any one of acetyl tributyl citrate, acetyl trioctyl citrate and trioctyl citrate.

[0028] Preferably, the material of the color film layer is any one of TPU color film (TPU: polyurethane) and EVA color film (EVA: ethylene-vinyl acetate copolymer), both of which are commercially available.

[0029] Preferably, the thickness of the wear-resistant layer is 0.4-0.6 mm, the thickness of the color film layer is 0.06-0.08 mm, and the thickness of the substrate layer is 2-3 mm.

[0030] The present invention also provides a method for preparing a hard wear-resistant non-PVC environmentally friendly stone plastic floor, comprising the following steps:

[0031] According to the raw material formula of the wear-resistant layer, each raw material is put into a high-speed mixer, mixed and stirred at 800-1000rpm and 80-90℃ for 7-10min, and then put into an extruder for extrusion molding to obtain the wear-resistant layer; wherein, the process conditions of the extrusion molding are: extrusion temperature 160-180℃, mold temperature 170-190℃, main machine speed 10-30rpm, and feeding speed 20-30rpm;

[0032] According to the raw material formula of the substrate layer, each raw material is put into a high-speed mixer, mixed and stirred at 800-1000rpm and 80-90℃ for 10-15min, and then put into an extruder for extrusion molding to obtain the substrate layer; wherein, the process conditions of the extrusion molding are: extrusion temperature 160-170℃, mold temperature 170-180℃, main machine speed 10-30rpm, and feeding speed 20-30rpm;

[0033] The wear-resistant layer, the color film layer and the substrate layer are stacked from top to bottom, and hot-pressed to obtain the hard wear-resistant non-PVC environmentally friendly stone plastic floor. The process conditions of hot-pressing are: hot-pressing temperature 155-170°C, hot-pressing pressure 5-15MPa, and hot-pressing time 40-60min.

[0034] Beneficial effects of the present invention:

[0035] The present invention provides a hard wear-resistant non-PVC environmentally friendly stone plastic floor. On the one hand, by using degradable PBAT resin to replace PVC, and collocating with specific reinforcing additives to form a base material layer, it is more green and environmentally friendly, and has excellent mechanical properties; on the other hand, by using specific functionalized polyurethane elastomers and modified fillers to form a wear-resistant layer, the wear resistance of the stone plastic floor is further improved and the service life is extended. The present invention also provides a preparation method of the above-mentioned hard wear-resistant environmentally friendly stone plastic floor, which has a simple process and high safety. DETAILED DESCRIPTION

[0036] The above-mentioned invention contents of the present invention are further described in detail below in conjunction with specific implementation methods. The embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the contents of the present invention and implement them accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.

[0037] PBAT resin, density: 1.3g / cm 3 , Melt index: 5g / 10min (2.16kg / 190℃, ASTM D1238).

[0038] EMA-g-GMA, density: 0.95 g / cm 3 , melt index: 10g / 10min (2.16kg / 190℃, ASTM D1238), grafting rate: 5.0%.

[0039] EVA-g-MAH, density: 0.94g / cm 3 , melt index: 11.5g / 10min (2.16kg / 190℃, ASTM D1238), grafting rate: 6.3%.

[0040] Heavy calcium carbonate, average particle size: 500 mesh.

[0041] Mica powder, average particle size: 800 mesh.

[0042] Polytetramethylene glycol, average molecular weight: 2000.

[0043] Nano-alumina, average particle size: 100nm.

[0044] Example 1

[0045] A hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises, from top to bottom, a wear-resistant layer, a color film layer and a base material layer.

[0046] The wear-resistant layer is made of the following raw materials in parts by weight: 95 parts by weight of functionalized polyurethane elastomer, 5 parts by weight of modified filler, and 0.5 parts by weight of antioxidant 1076.

[0047] The substrate layer is made of the following raw materials in parts by weight:

[0048] 40 parts by weight of PBAT resin, 60 parts by weight of heavy calcium carbonate, 15 parts by weight of mica powder, 4 parts by weight of reinforcing aid, 0.2 parts by weight of stabilizer N,N'-di(2,6-diisopropylphenyl)carbodiimide, and 0.3 parts by weight of plasticizer tributyl acetyl citrate. The reinforcing aid is a mixture of EMA-g-GMA and EVA-g-MAH in a weight ratio of 3:2.

[0049] The functionalized polyurethane elastomer is prepared by the following method:

[0050] 30 parts by weight of 1,3,5,7,9-pentamethylcyclopentasiloxane and 15 parts by weight of allyl succinic anhydride are added to 120 parts by weight of N,N-dimethylformamide, and heated to 75°C at 250rpm under nitrogen protection, and then 0.2 parts by weight of Custer catalyst is added to keep the temperature for 3 hours, and N,N-dimethylformamide is recovered by vacuum distillation to obtain succinic anhydride grafted cyclopentasiloxane; 12 parts by weight of succinic anhydride grafted cyclopentasiloxane, 8 parts by weight of heptamethylphenyl cyclotetrasiloxane, and 0.15 parts by weight of tetramethylammonium hydroxide are added to 80 parts by weight of N,N-dimethylformamide, and heated to 75°C at 70 ℃, 250rpm for 1h, then add 0.2 weight parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and continue to react for 0.5h, and recover N,N-dimethylformamide by reduced pressure distillation to obtain modified polysiloxane; 12 weight parts of polytetrahydrofuran ether diol, 25 weight parts of diphenylmethane-4,4'-diisocyanate, 5 weight parts of modified polysiloxane, 3 weight parts of 1,4-butanediol and 0.12 weight parts of dibutyltin dilaurate are mixed, reacted at 75℃, 150rpm for 2.5h, and dried after completion to obtain a functionalized polyurethane elastomer.

[0051] The modified filler is prepared by the following method:

[0052] 1.2 parts by weight of N-aminoethyl-3-aminopropylmethyldimethoxysilane are added to 25 parts by weight of 60wt% ethanol aqueous solution, stirred at 50°C and 200rpm for 20min, then 3 parts by weight of nano-alumina and 75 parts by weight of anhydrous ethanol are added and stirred for 1.5h, filtered and dried to obtain surface-treated nano-alumina; 0.6 parts by weight of 2-furanacetic acid, 2.4 parts by weight of surface-treated nano-alumina and 0.05 parts by weight of 4-dimethylaminopyridine are added to 20 parts by weight of tetrahydrofuran, reacted at 55°C under nitrogen protection for 12h, filtered and dried to obtain a modified filler.

[0053] A method for preparing a hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises the following steps:

[0054] According to the raw material formula of the wear-resistant layer, each raw material was put into a high-speed mixer, mixed and stirred at 900 rpm and 85°C for 8 minutes, and then put into an extruder for extrusion molding to obtain a wear-resistant layer; wherein, the process conditions of the extrusion molding are: extrusion temperature 170°C, mold temperature 180°C, main machine speed 20rpm, and feeding speed 25rpm;

[0055] According to the raw material formula of the substrate layer, each raw material was put into a high-speed mixer, mixed and stirred at 900 rpm and 85°C for 12 minutes, and then put into an extruder for extrusion molding to obtain the substrate layer; wherein, the process conditions of the extrusion molding are: extrusion temperature 165°C, mold temperature 175°C, main machine speed 20rpm, and feeding speed 25rpm;

[0056] The wear-resistant layer, the color film layer and the base material layer are stacked from top to bottom, and hot-pressed to obtain the hard wear-resistant non-PVC environmentally friendly stone plastic floor. The thickness of the wear-resistant layer is 0.5 mm, the thickness of the color film layer is 0.07 mm, the material is TPU color film, and the thickness of the base material layer is 2.5 mm; the process conditions of hot-pressing are: hot-pressing temperature 160°C, hot-pressing pressure 10 MPa, and hot-pressing time 50 min.

[0057] Example 2

[0058] A hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises, from top to bottom, a wear-resistant layer, a color film layer and a base material layer.

[0059] The wear-resistant layer is made of the following raw materials in parts by weight: 95 parts by weight of functionalized polyurethane elastomer, 5 parts by weight of modified filler, and 0.5 parts by weight of antioxidant 1076.

[0060] The substrate layer is made of the following raw materials in parts by weight:

[0061] 40 parts by weight of PBAT resin, 60 parts by weight of heavy calcium carbonate, 15 parts by weight of mica powder, 4 parts by weight of reinforcing aid, 0.2 parts by weight of stabilizer N,N'-di(2,6-diisopropylphenyl)carbodiimide, and 0.3 parts by weight of plasticizer tributyl acetyl citrate. The reinforcing aid is a mixture of EMA-g-GMA and EVA-g-MAH in a weight ratio of 3:2.

[0062] The functionalized polyurethane elastomer is prepared by the following method:

[0063] 12 parts by weight of 1,3,5,7,9-pentamethylcyclopentasiloxane, 8 parts by weight of heptamethylphenyl cyclotetrasiloxane and 0.15 parts by weight of tetramethylammonium hydroxide are added to 80 parts by weight of N,N-dimethylformamide, and the mixture is reacted at 70°C and 250 rpm for 1 hour, and then 0.2 parts by weight of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added to continue the reaction for 0.5 hour, and N,N-dimethylformamide is recovered by vacuum distillation to obtain a modified polysiloxane; 12 parts by weight of polytetrahydrofuran ether diol, 25 parts by weight of diphenylmethane-4,4'-diisocyanate, 5 parts by weight of modified polysiloxane, 3 parts by weight of 1,4-butanediol and 0.12 parts by weight of dibutyltin dilaurate are mixed, and the mixture is reacted at 75°C and 150 rpm for 2.5 hours, and then dried to obtain a functionalized polyurethane elastomer.

[0064] The modified filler is the same as that in Example 1.

[0065] The preparation method of a hard wear-resistant non-PVC environmentally friendly stone plastic floor is the same as that in Example 1.

[0066] Example 3

[0067] A hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises, from top to bottom, a wear-resistant layer, a color film layer and a base material layer.

[0068] The wear-resistant layer is made of the following raw materials in parts by weight: 95 parts by weight of functionalized polyurethane elastomer, 5 parts by weight of modified filler, and 0.5 parts by weight of antioxidant 1076.

[0069] The substrate layer is made of the following raw materials in parts by weight:

[0070] 40 parts by weight of PBAT resin, 60 parts by weight of heavy calcium carbonate, 15 parts by weight of mica powder, 4 parts by weight of reinforcing aid, 0.2 parts by weight of stabilizer N,N'-di(2,6-diisopropylphenyl)carbodiimide, and 0.3 parts by weight of plasticizer tributyl acetyl citrate. The reinforcing aid is a mixture of EMA-g-GMA and EVA-g-MAH in a weight ratio of 3:2.

[0071] The functionalized polyurethane elastomer is prepared by the following method:

[0072] 12 parts by weight of polytetramethylene glycol, 25 parts by weight of diphenylmethane-4,4'-diisocyanate, 5 parts by weight of commercially available polysiloxane, 3 parts by weight of 1,4-butanediol and 0.12 parts by weight of dibutyltin dilaurate were mixed, reacted at 75°C and 150 rpm for 2.5 hours, and dried after completion to obtain a functionalized polyurethane elastomer. Among them, the commercially available polysiloxane used was poly(dimethylsiloxane) with a viscosity of 500 cSt (25°C).

[0073] The modified filler is the same as that in Example 1.

[0074] The preparation method of a hard wear-resistant non-PVC environmentally friendly stone plastic floor is the same as that in Example 1.

[0075] Example 4

[0076] A hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises, from top to bottom, a wear-resistant layer, a color film layer and a base material layer.

[0077] The wear-resistant layer is made of the following raw materials in parts by weight: 95 parts by weight of functionalized polyurethane elastomer, 5 parts by weight of nano-aluminum oxide, and 0.5 parts by weight of antioxidant 1076.

[0078] The substrate layer is made of the following raw materials in parts by weight:

[0079] 40 parts by weight of PBAT resin, 60 parts by weight of heavy calcium carbonate, 15 parts by weight of mica powder, 4 parts by weight of reinforcing aid, 0.2 parts by weight of stabilizer N,N'-di(2,6-diisopropylphenyl)carbodiimide, and 0.3 parts by weight of plasticizer tributyl acetyl citrate. The reinforcing aid is a mixture of EMA-g-GMA and EVA-g-MAH in a weight ratio of 3:2.

[0080] The functionalized polyurethane elastomer is the same as that in Example 1.

[0081] The preparation method of a hard wear-resistant non-PVC environmentally friendly stone plastic floor is the same as that in Example 1.

[0082] Example 5

[0083] A hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises, from top to bottom, a wear-resistant layer, a color film layer and a base material layer.

[0084] The wear-resistant layer is made of the following raw materials in parts by weight: 95 parts by weight of functionalized polyurethane elastomer, 5 parts by weight of modified filler, and 0.5 parts by weight of antioxidant 1076.

[0085] The substrate layer is made of the following raw materials in parts by weight:

[0086] 40 parts by weight of PBAT resin, 60 parts by weight of heavy calcium carbonate, 15 parts by weight of mica powder, 4 parts by weight of reinforcing agent, 0.2 parts by weight of stabilizer N,N'-di(2,6-diisopropylphenyl)carbodiimide, and 0.3 parts by weight of plasticizer tributyl acetyl citrate. The reinforcing agent is EMA-g-GMA.

[0087] The functionalized polyurethane elastomer is the same as that in Example 1.

[0088] The modified filler is the same as that in Example 1.

[0089] The preparation method of a hard wear-resistant non-PVC environmentally friendly stone plastic floor is the same as that in Example 1.

[0090] Example 6

[0091] A hard wear-resistant non-PVC environmentally friendly stone plastic floor comprises, from top to bottom, a wear-resistant layer, a color film layer and a base material layer.

[0092] The wear-resistant layer is made of the following raw materials in parts by weight: 95 parts by weight of functionalized polyurethane elastomer, 5 parts by weight of modified filler, and 0.5 parts by weight of antioxidant 1076.

[0093] The substrate layer is made of the following raw materials in parts by weight:

[0094] 40 parts by weight of PBAT resin, 60 parts by weight of heavy calcium carbonate, 15 parts by weight of mica powder, 4 parts by weight of reinforcing agent, 0.2 parts by weight of stabilizer N,N'-di(2,6-diisopropylphenyl)carbodiimide, 0.3 parts by weight of plasticizer acetyl tributyl citrate. The reinforcing agent EVA-g-MAH.

[0095] The functionalized polyurethane elastomer is the same as that in Example 1.

[0096] The modified filler is the same as that in Example 1.

[0097] The preparation method of a hard wear-resistant non-PVC environmentally friendly stone plastic floor is the same as that in Example 1.

[0098] Test Example 1

[0099] The mechanical properties of the environmentally friendly stone plastic floor prepared in the above Examples 1, 5, and 6 were measured. The tensile strength was measured according to the reference standard GB / T 1040.2-2022, and the notched impact strength was measured according to the reference standard GB / T 1843-2008. The results are shown in Table 1.

[0100] Table 1 Mechanical properties test results of environmentally friendly stone plastic floor

[0101] Tensile strength / Mpa <![CDATA[Notched impact strength / kJ / m 2 > Example 1 27.6 15.8 Example 5 22.9 12.3 Example 6 21.5 11.8

[0102] Test Example 2

[0103] The wear resistance of the environmentally friendly stone plastic floor prepared in the above examples 1-4 was measured. The test conditions of the friction coefficient were: 45# steel The steel ball has a roughness of 1 μm, a rotation test method, a radius of 10 mm, a rotation rate of 200 r / min, and a load of 80 N. The results are shown in Table 2.

[0104] Table 2 Wear resistance test results of environmentally friendly stone plastic floor

[0105] Friction coefficient Example 1 0.20 Example 2 0.29 Example 3 0.33 Example 4 0.38

[0106] By comparing the above embodiments, it can be seen that the environmentally friendly stone plastic floor prepared in Example 1 has excellent mechanical properties and wear resistance. The reason is that the present invention adopts functionalized polyurethane elastomer and modified filler in the wear-resistant layer of the environmentally friendly stone plastic floor, and adopts reinforcing additives in the substrate layer of the environmentally friendly stone plastic floor, thereby effectively improving the mechanical properties and wear resistance of the stone plastic floor. Compared with Example 1, the functionalized polyurethane elastomer and modified filler prepared by a specific method are not used in Examples 2-4. It can be seen from Table 2 that the wear resistance of the stone plastic floor is reduced to a certain extent. Compared with Example 1, no specific reinforcing additive is used in Examples 5-6 to improve the performance of the substrate. It can be seen from Table 1 that the mechanical properties of the stone plastic floor are reduced. This shows that Examples 2-6 do not adopt the necessary technical solutions of the present invention, resulting in obvious deterioration in the corresponding performance tests, which further demonstrates the importance of the necessary technical solutions defined by the present invention to its technical effects.

[0107] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A hard wear-resistant non-PVC environmentally friendly stone plastic floor, characterized by: From top to bottom, it includes: a wear-resistant layer, a color film layer and a substrate layer; the wear-resistant layer includes the following raw materials: functionalized polyurethane elastomer, modified filler, antioxidant; the substrate layer includes the following raw materials: PBAT resin, heavy calcium carbonate, mica powder, reinforcing additive, stabilizer, plasticizer.

2. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The functionalized polyurethane elastomer is prepared by the following method: 1,3,5,7,9-pentamethylcyclopentasiloxane and allyl succinic anhydride are added to N,N-dimethylformamide, heated under nitrogen protection, and then Custer catalyst is added for reaction, and vacuum distillation is performed to obtain succinic anhydride grafted cyclopentasiloxane; succinic anhydride grafted cyclopentasiloxane, heptamethylphenyl cyclotetrasiloxane, and tetramethylammonium hydroxide are added to N,N-dimethylformamide, heated for reaction, and then 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added for further reaction, and vacuum distillation is performed to obtain modified polysiloxane; polytetrahydrofuran ether diol, diphenylmethane-4,4'-diisocyanate, modified polysiloxane, 1,4-butanediol and dibutyltin dilaurate are mixed, heated for reaction, and dried after completion to obtain a functionalized polyurethane elastomer.

3. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The modified filler is prepared by the following method: N-aminoethyl-3-aminopropylmethyldimethoxysilane is added to an ethanol aqueous solution, heated and stirred, and then nano-alumina and anhydrous ethanol are added and stirred continuously, filtered, and dried to obtain surface-treated nano-alumina; 2-furanacetic acid, surface-treated nano-alumina, and 4-dimethylaminopyridine are added to tetrahydrofuran, heated for reaction under nitrogen protection, filtered, and dried to obtain a modified filler.

4. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The antioxidant is at least one of antioxidant 1076, antioxidant 1010, and antioxidant DSTDP.

5. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The reinforcing aid is EMA-g-GMA and / or EVA-g-MAH.

6. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The stabilizer is any one of N,N'-di(2,6-diisopropylphenyl)carbodiimide, polycarbodiimide, and N,N'-diisopropylcarbodiimide.

7. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The plasticizer is any one of acetyl tributyl citrate, acetyl trioctyl citrate and trioctyl citrate.

8. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The wear-resistant layer is made of the following raw materials in parts by weight: 90-100 parts by weight of functionalized polyurethane elastomer, 3-7 parts by weight of modified filler, and 0.3-0.6 parts by weight of antioxidant.

9. The hard wear-resistant non-PVC environmentally friendly stone plastic floor as claimed in claim 1, characterized in that: The substrate layer is made of the following raw materials in parts by weight: 30-50 parts by weight of PBAT resin, 50-70 parts by weight of heavy calcium carbonate, 10-20 parts by weight of mica powder, 3-5 parts by weight of reinforcing agent, 0.1-0.3 parts by weight of stabilizer, and 0.2-0.4 parts by weight of plasticizer.

10. The method for preparing the hard wear-resistant non-PVC environmentally friendly stone plastic floor according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the raw material formula of the wear-resistant layer, each raw material is put into a high-speed mixer for mixing and stirring, and then put into an extruder for extrusion molding to obtain a wear-resistant layer; According to the raw material formula of the substrate layer, each raw material is put into a high-speed mixer for mixing and stirring, and then put into an extruder for extrusion molding to obtain the substrate layer; The wear-resistant layer, the color film layer and the base material layer are stacked in sequence from top to bottom, and hot-pressed to obtain the hard wear-resistant non-PVC environmentally friendly stone plastic floor.

Citation Information

Patent Citations

  • PVC stone-plastic floor and production method thereof

    CN107627687A

  • Stone-plastic floor and preparation method thereof

    CN109057241A